2019
DOI: 10.1080/23322039.2019.1568849
|View full text |Cite
|
Sign up to set email alerts
|

Management of shadow banks for economic and financial stability in South Africa

Abstract: The global increase in the regulation of banks has encouraged the channeling of investment funds into less regulated institutions such as shadow banks to avoid restriction. Shadow banks are institutions that operate outside the regulatory framework of the traditional banking system and because of that, they lack adequate safety compared to the traditional banks. These among others have raised serious concerns, especially after the recent financial crisis as they see these institutions as a major source of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The growth of SB and the inconclusiveness of the debate on SB prospects make studies addressing its implications on financial stability crucial. Some of the studies addressing such implications focused on specific components of SB (e.g., Culp 2013;Bengtsson 2013), and others addressed the overall SB sector (e.g., Barth et al 2015;Liang 2016a, Tsai 2016Zhou and Tewari 2019a, b;Ilesanmi and Tewari 2019). Bengtsson (2013) conducted a study on the European economy and reported that there is a lack of transparency regarding the composition of Money Market Fund (MMFs) assets making it difficult for European MMF investors to distinguish between MMFs based on their asset quality.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The growth of SB and the inconclusiveness of the debate on SB prospects make studies addressing its implications on financial stability crucial. Some of the studies addressing such implications focused on specific components of SB (e.g., Culp 2013;Bengtsson 2013), and others addressed the overall SB sector (e.g., Barth et al 2015;Liang 2016a, Tsai 2016Zhou and Tewari 2019a, b;Ilesanmi and Tewari 2019). Bengtsson (2013) conducted a study on the European economy and reported that there is a lack of transparency regarding the composition of Money Market Fund (MMFs) assets making it difficult for European MMF investors to distinguish between MMFs based on their asset quality.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
“…It was additionally found that the SB sector positively impacts aggregate firm profitability (Zhou and Tewari 2019a, b). Another study argued that SB in South Africa is beneficial as it provides alternative sources of credit and extends economic investment opportunities; yet, lack of transparency, management, and regulations poses great risk to the economy (Ilesanmi and Tewari 2019). In contrast, a study on the Canadian economy suggested that Canada's productivity problem could be solved through innovation.…”
Section: Sb and Financial Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2007/08 global financial crisis (GFC) which emanated from the United States and spread to other developed and emerging countries resulted in large-scale losses in most economies around the globe (Cunningham and Friedrich, 2016;Ilesanmi and Tewari, 2019a). The devastating effects of the GFC have led to a renewed, global interest in the development of an early warning signal (EWS) model with the purpose of alerting policymakers and other stakeholders to the possibility of the occurrence of a crisis (Ilesanmi and Tewari, 2019b).…”
Section: Introductionmentioning
confidence: 99%